The relationship between ‘position-port’, ‘hardport’ and ‘soft-port’ characteristics and port performance: conceptual models - Caldeirinha, Vitor (2022)
This research study attempts to conceptualize models based on the relationship between characterization factors and port performance. By selecting a universe of the 230 largest European ports in terms of cargo throughput, 43 valid answers were obtained. Factor analysis and K–W (Kruskal–Wallis) tests were carried out taking as a reference the port performance theory. Findings reveal the existence of a relationship between port performance and its characterization factors, delving into the development of conceptualized models that contribute to deepen the knowledge of port competition structure and dynamics within Europe.